A New Parasitic Chytrid, Staurastromyces oculus (Rhizophydiales, Staurastromycetaceae fam. nov.), Infecting the Freshwater Desmid Staurastrum sp. - Wyngaert, Silke Van den (2017)
Chytrids are a diverse group of ubiquitous true zoosporic fungi. The recent molecular discovery of a large diversity of undescribed chytrids has raised awareness on their important, but so far understudied ecological role in aquatic ecosystems. In the pelagic zone, of both freshwater and marine ecosystems, many chytrid species have been morphologically described as parasites on almost all major groups of phytoplankton. However, the majority of these parasitic chytrids has rarely been isolated and lack DNA sequence data, resulting in a large proportion of “dark taxa” in databases. Here, we report on the isolation and in-depth morphological, molecular and host range characterization of a chytrid infecting the common freshwater desmid Staurastrum sp. We provide first insights on the metabolic activity of the different chytrid development stages by using the vital dye FUN®-1 (2-chloro-4-[2,3-dihydro-3-methyl-[benzo-1,3-thiazol-2-yl]-methylidene]-1-phenylquinolinium iodide). Cross infection experiments suggest that this chytrid is an obligate parasite and specific for the genus Staurastrum sp. Phylogenetic analysis, based on ITS1-5.8S-ITS2 and 28S rDNA sequences, placed it in the order Rhizophydiales. Based on the unique zoospore ultrastructure, combined with thallus morphology, and molecular phylogenetic placement, we describe this parasitic chytrid as a new genus and species Staurastromyces oculus, within a new family Staurastromycetaceae.